CO2 Mineralization: Production of Precipitated Calcium Carbonate as a Method of CO2 Utilization - H. Berahim, N; M. Lahuri, H; G. Mohd Noh, M; S. Onn, M; Othman, R (International Journal of Engineering and Technology, 2019)
CO2 utilization into minerals is one of the most efficient methodologies although much research concerns the utilization of CO2 to produce chemicals. The production of precipitated calcium carbonate (PCC) from three different starting materials has been reported. The gas-liquid reaction is carried out by bubbling carbon dioxide into a solution of lime products with fixed parameters of 99% CO2 purity, 4.0 L/min of flow rate and 1500 rpm stirring rate at atmospheric pressure. The PCC was then characterized for X-Ray diffraction (XRD), field emission scanning electron microscopy (FESEM), X-Ray fluorescence (XRF) and particle size. Experimental results indicate that the PCC produced from quick lime showed the highest yield of 17.27 g, however there is no significant difference for both carbide lime and hydrated lime at 12.04 g and 11.57 g respectively. Morphology, phase structure and particle size of PCC produced reveals insignificant influence with different starting materials. Producing PCC from CO2 and natural minerals can be a potential method of reducing CO2 emissions by locking-up CO2 in a stable mineral form, whilst at the same time turning low quality natural minerals into high valuable products.Â Â Â